Design of a hydrokinetic turbine capable of satisfying electricity demand for housing on the margin of the Magdalena river through analysis by finite elements - Fabregas Villegas, Jonathan; Santamaria De La Cruz, Henry; Márquez Santos, Mauricio; Fontalvo Calvo, Camilo; Carpintero Durango, Javier; Villa Dominguez, Jennifer (International Journal of Engineering and Technology, 2019)
This research is aimed to design a hydrokinetic turbine for electric generation taking advantage of available energy of the Magdalena River, which has a great flow near to its mouth in the Atlantic Ocean of Northern Colombian. The turbine design consists of a tri-bladed horizontal axis turbine totally submerged; the rotor is fixed to a metallic platform with tanks acting as floats. It also contains an asynchronous electric engine as a generator and electrical lines. The turbine power shaft is transmitted to the engine by a system of toothed belts, which performs the role of gearbox and multiplier. As a result, CFD simulations shows several variables of interest in order to evaluate power generation, such as torque, angular velocity, power, turbine efficiency, and hydrokinetic and structural analysis are obtained by means of finite elements.Â